2002
DOI: 10.1063/1.1478154
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal dependence of contact resistivity on hole concentration in nonalloyed ohmic contacts to p-GaN

Abstract: The dependence of contact resistivity on hole concentration has been investigated for nonalloyed Pd contacts to p-GaN. The hole concentration was varied by changing the Mg concentration, [Mg], in p-GaN. The p-GaN having the [Mg] of 4.5×1019 cm−3 showed the hole concentration of 2.2×1017 cm−3, where contact resistivity was measured as 8.9×10−2 Ω cm2. When the [Mg] increased to 1.0×1020 cm−3, the hole concentration was significantly reduced to 2.0×1016 cm−3. Nevertheless, the Pd contacts on the p-GaN displayed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 13 publications
4
40
0
Order By: Relevance
“…The p-layer with low hole density but with rather high Mg impurity content is more suitable to the LED structure. The similar phenomena were reported in ohmic contacts [7]. And the contact resistivity was explained by predominant current flow at the Pd/p-GaN interface through a deep level defect band.…”
Section: Resultsmentioning
confidence: 57%
“…The p-layer with low hole density but with rather high Mg impurity content is more suitable to the LED structure. The similar phenomena were reported in ohmic contacts [7]. And the contact resistivity was explained by predominant current flow at the Pd/p-GaN interface through a deep level defect band.…”
Section: Resultsmentioning
confidence: 57%
“…The minimum contact resistivity was measured as 9.4 × 10 -4 Ω cm 2 . This result suggests that high Mg doping in the p-contact layer causes defect states, and the predominant current flows at the contact/p-GaN interface through a deep level defect band, rather than the valence band [3,4]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…For this purpose, the proper p-doping condition is necessary. We have already reported that the introduction of a thin layer having high [Mg] between Pd/Pt/Au and moderating p-doped GaN layer greatly increases the current flow at the interface [3]. .…”
Section: Resultsmentioning
confidence: 99%
“…The Pd provides good specific contact resistance in the as-deposited state, therefore, Pd was used as an ohmic material to narrow TLM. [27,28] Figure 5 is a scanning electron microscope (SEM) image of the fabricated narrow TLM patterns with narrow (2-μm in width) mesa structures. The cross-sectional SEM image (inset) shows that the narrow TLM pattern was well fabricated on the wing region of the LEO GaN.…”
Section: Influence Of Micro-structural Defects On the Carrier Transportmentioning
confidence: 99%
“…As for the design of p-GaN:Mg contact layer, Kwak et al reported the pGaN contact layer having a high Mg-doped thin cap layer. [27,43,44] In this design, an additional thin layer (10 nm) having a high [Mg] (1x10 20 cm -3 ) was grown on p-GaN having the [Mg] of 4.5x10 19 cm -3 . In x-ray diffraction, the full width at half maximum values of (0002) and (1ī02) for the p-GaN contact layer having a high Mg-doped thin cap layer were identical to those for the p-GaN contact layer without the cap layer, which implies that the microstructure was not changed by the addition of the thin layer.…”
Section: Design Of P-gan Contact Layer To Minimize Operating Voltage mentioning
confidence: 99%